Spiral Wave Generation in a Vortex Electric Field - Yuan, Xiao-Ping (晓平 袁); Chen, Jiang-Xing (江星 陈); Zhao, Ye-Hua (叶华 赵); Lou, Qin (钦楼); Wang, Lu-Lu (璐璐 王); Shen, Qian (谦沈) (Chinese physics letters, 2011)
The effect of a vortical electric field on nonlinear patterns in excitable media is studied. When an appropriate vortex electric field is applied, the system exhibits pattern transition from chemical turbulence to spiral waves, which possess the same chirality as the vortex electric field. The underlying mechanism of this is discussed. We also show the meandering behavior of a spiral under the taming of a vortex electric field. The results obtained here may contribute to control strategies of patterns on surface reaction.